The Potentials Of Artificial Intelligence In Stimulating Motivation And Improving Performance Of Undergraduates In Foreign Languages (Journal of Namibian Studies : History Politics Culture, 2023)
Motivation plays huge role in improving the performance of foreign language learners in developing different language skills. Various factors have been discussed to stimulate motivation in foreign language learning. Artificial intelligence tools have significantly permeated almost all the aspects of our daily functionality, with glaring impact on the education system. This study pursues an understanding of the role of various artificial intelligence tools for teaching foreign languages in stimulation motivation and improving the performance of undergraduates. Using a stratified survey design, 250 respondents were pooled for this study, including 50 lecturers, and 200 undergraduates in foreign language education. Questionnaires were distributed electronically to the participants who were pooled across different universities. Analysis was conducted using relevant statistical measures, and the findings were presented in descriptive statistics tables. The findings indicate that over 80% of the undergraduates and lecturers acknowledge that they have used AI models in facilitating foreign language teaching and learning. Also, over 70% of the lecturers affirm that the performance of their students has significantly improved since they integrated AI models in foreign language education. Over 70% of the lecturers affirm that real-time feedback mechanisms, Chat Bots, automated reward systems, and other tools have solved the limitations of traditional teaching tools, and enhanced speaking, writing and reading efficiency of the learners. Over 75% of the undergraduates that AI models have stimulated them, motivated them, and assisted them to show more interest in their foreign language courses, and also help them to practice their foreign language skills out of class. It is thus concluded that AI exhibit huge potentials to mitigate the limitations of conventional teaching and learning tools.